A new method for determining aflatoxins in groundnut and groundnut cake using fourier transform infrared spectroscopy with attenuated total reflectance - Mirghani, M. E. S.; Che Man, Y. B.; Jinap, S.; Baharin, B. S.; Bakar, J. (Wiley, 2001)
A new analytical method was developed for the determination of aflatoxins in groundnut and groundnut cakes by Fourier transform infrared (FTIR) spectroscopy using horizontal attenuated total reflectance technique. Groundnut and groundnut cake samples were used in this study. The wavelengths were selected for the four types of aflatoxins-B1, B2, G1, and G2 - and the standards prepared for each by spiking some clean sample with the aflatoxins in concentrations of 0-1200 parts per billion. A partial least square regression was used to derive the calibration models for each toxin. The coefficients of determination (R2) of the calibration model were computed for the FTIR spectroscopy predicted values vs. actual values of aflatoxins in parts per billion. The R2 was found to be 0.9911, 0.9859, 0.9986, and 0.9789 for aflatoxins B1, B2, G1, and G2, respectively. Standard errors of calibration for groundnut samples were found to be 1.80, 2.03, 1.42, and 2.05 for aflatoxins B1, B2, G1, and G2, respectively. Calibration models were validated with an independent set of samples. The R2 of validation models were computed. The SD of the difference for repeatability of the FTIR method was found to be better than that of the chemical method. Based on the results obtained, FTIR spectroscopy can be a useful instrumental method for determining aflatoxins in oilseeds and oilseed cakes. With its speed and ease of data manipulation by computer software, it is a possible alternative to the standard wet chemical methods for a rapid and accurate routine determination of aflatoxin levels in food and feed.